Pedocomplex buried under the Cabin of Peter the Great in St. Petersburg (1703): Genesis, properties and paleoenvironmental inferences. (30th August 2022) - Rusakov, Alexey; Fedorova, Maria; Makeev, Alexander; Ludikova, Anna; Savelieva, Larisa; Golyeva, Alexandra; Lebedeva, Marina; Sorokin, Petr; Rusakova, Elena; Subetto, Dmitry
Abstract: A study was conducted on the buried soils identified at the base of the foundation of the Cabin of Peter the Great in Saint Petersburg, Russia, to help trace the Late Holocene landscape evolution in the lower reaches of the Neva River. The Cabin is a small wooden house, which was the first residence of Peter the Great in a newly emerged Saint-Petersburg. The house was built of pine logs on the Neva River's right bank. The time of its construction is now regarded as the city's founding date (1703). The pedocomplex with two buried soils has not been truncated and retains a record of the depositional environment, pedogenesis, vegetation history, and human activity before the construction of the city of Saint Petersburg. This pedocomplex was studied using various field and laboratory methods including soil morphology at macro-, meso-, and microlevels, and a full set of microbiomorphic analyses (diatoms, pollen, spores, phytoliths, plant detritus, and amorphous organic matter) supported by radiocarbon dating. The sediment sequence was formed in a contrasting depositional environment. The microbiomorphic studies indicated that the initial substrate was formed in aquatic environments. The analysis of diatoms suggested that these sediments were accumulated as a result of the River Neva breakthrough from Lake Ladoga to the Gulf of Finland ca 3500 yrs BP, which provided additional evidence for the River Neva formation. Soil analyses revealed two inundation events, with the earlier flood related to the termination of the Lake Ladoga transgression (LT) and the breakthrough of the Neva River, whereas the latter flood was likely to be connected with an increase of the fluvial activity. Those two inundation events were followed by two stages of pedogenesis. Both soils indicated the hiatus in sedimentation and were represented by Subquatic Umbric Gleysols that were the most widespread indigenous soils in the XVII century. The pollen data suggest that human impact started at ca 800 yrs BP and eventually resulted in the deforestation and the initial agricultural exploration of the study area. Saint Petersburg is the only large city in Russia that could be at risk from flooding if the sea level rises due to continuing global warming. Our research shows that the city's historical center was twice subjected to flooding in the Late Holocene, even without rises in the sea level. Therefore, the detailed analysis of the environmental dynamics within the Lower Neva area and the assessment of its possible consequences for the city are of great importance.